Estrogen markedly reduces circulating low-density neutrophils and enhances pro-tumoral gene expression in neutrophil of tumour-bearing mice - Lim, Chew Leng (2021)
Neutrophils are important for immune surveillance of tumour cells. Neutrophils may also be epigenetically programmed in the tumour microenvironment to promote tumour progression. In addition to the commonly known high-density neutrophils (HDN) based on their separation on density gradient, recent studies have reported the presence of high levels of low-density neutrophils (LDN) in tumour-bearing mice and cancer patients. We reported previously that estrogen promotes the growth of estrogen receptor α-negative mammary tumours in mice undergoing mammary involution through stimulating pro-tumoral activities of neutrophils in the mammary tissue.